2021
DOI: 10.1097/txd.0000000000001130
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mentoring as an Avenue to Explore in Kidney Transplantation: Kidney Transplant Recipients’ Perspectives on Peer Mentoring

Abstract: Background. Kidney transplant recipients (KTRs) face numerous challenges following transplantation. Given that healthcare professionals do not necessarily have first-hand experience living with or waiting for a transplant, it may be hard for them to communicate with and help patients when it comes to transplant-related issues. KTRs have experiential knowledge, which could enable them to help other patients going through similar situations. Peer mentoring involves pairing mentees with individuals who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In order to help kidney transplant recipients improve their self-management skills, prolong graft function, and maintain psychological well-being, clinical nurses should concentrate on meeting their emotional and social support needs (Pisanti et al, 2014;Been-Dahmen et al, 2018). Some researchers have pointed out that through the adoption of a kidney transplant patient support program, sharing disease experiences may improve patients' postoperative loneliness and assists them in increasing their selfconfidence after kidney transplantation (Pomey et al, 2021). Medical staff should provide appropriate medical support services, while clinical nurses should fully mobilize the patient's family members to encourage them to actively participate in the recovery and care of the kidney transplant recipient.…”
Section: Variables Psychosocial Adaptationmentioning
confidence: 99%
“…In order to help kidney transplant recipients improve their self-management skills, prolong graft function, and maintain psychological well-being, clinical nurses should concentrate on meeting their emotional and social support needs (Pisanti et al, 2014;Been-Dahmen et al, 2018). Some researchers have pointed out that through the adoption of a kidney transplant patient support program, sharing disease experiences may improve patients' postoperative loneliness and assists them in increasing their selfconfidence after kidney transplantation (Pomey et al, 2021). Medical staff should provide appropriate medical support services, while clinical nurses should fully mobilize the patient's family members to encourage them to actively participate in the recovery and care of the kidney transplant recipient.…”
Section: Variables Psychosocial Adaptationmentioning
confidence: 99%
“… 36 - 38 As we have shown, KTRs viewed peer support and peer mentoring as a way of addressing transplant concerns and relieving loneliness and isolation. 39 In the present study, sharing self-narratives both before and during the creative writing workshops provided opportunities for normalization and relativization. In addition to the impacts of sharing self-narratives, during the creative writing workshops a unique type of learning arose from the group-facilitated reflection around stories.…”
Section: Discussionmentioning
confidence: 70%
“… 38 , 39 Participants in a recent exploratory study on peer mentorship for posttransplant patients reported that peer support provided a convenient and user-friendly way to address transplant-related concerns. 40 Peer mentorship has also been shown to be a valuable way of creating a community to help alleviate loneliness and isolation, which is common among posttransplant patients. 40 Digital stories do differ from traditional peer mentoring because of the unidirectional nature of the communication.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Peer mentorship has also been shown to be a valuable way of creating a community to help alleviate loneliness and isolation, which is common among posttransplant patients. 40 Digital stories do differ from traditional peer mentoring because of the unidirectional nature of the communication. However, in a world of remote telemedicine and difficulty matching real-life mentors with patients or family members/friends in person, viewing these stories may be a valuable starting point, particularly for those who cannot come to a transplant center to meet others.…”
Section: Discussionmentioning
confidence: 99%